Behavioral Drivers of Investment Decisions among Generation Z: The Roles of Expected Return (CAPM) and Risk Perception - Muhamad Fajar Oktara; Nataliana Bebasari (Talent: Journal of Economics and Business, 2026)
This study addresses the limited integration of traditional financial theory and behavioral perspectives in explaining youth investment decisions, particularly in emerging market contexts. This study aims to analyze the contribution of expected return based on the Capital Asset Pricing Model (CAPM) and risk perception to the investment decisions of Generation Z in Bekasi Regency, thereby advancing theoretical understanding by integrating CAPM-based expected return with behavioral risk perception variables into a unified framework that explains how rational financial expectations and psychological risk evaluations jointly shape youth investment decision-making. A quantitative approach was employed using primary data collected through questionnaires distributed to 62 Generation Z respondents who had experience in capital market investment. The data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 3.0 software. The results indicate that expected return (CAPM) has a positive and significant effect on investment decisions, while risk perception significantly influences more rational and cautious investment behavior. These findings suggest that Generation Z considers not only potential returns but also the inherent risks of investment instruments before making decisions. This study provides empirical evidence enriching the literature on youth investment behavior and offers practical insights for policymakers and financial institutions in designing more effective investment education and financial literacy programs.